Factores de risco e factores de protecção de comportamentos delinquentes em adolescentes do Porto - João Marques Teixeira (2004)
The author presents the results of a research concerning the self-reported delinquency in a sample of 589 adolescents living in Oporto. An analysis of risk and protector factors was conducted in order to determine the nature of the relations between high exposition to risk and the prevalence of behavioural problems. The fact that the results suggest no relation between risk and protection levels, indicating that these two types of factors act independently, is in opposition to Rutter and Landerman's buffering hypothesis. In addition, these results suggest that risk factors are exclusive predictors of adolescent transgressive behaviors, while risk and protector factors together predict criminal behaviors. Considering these results the author concludes that delinquency preventive programs must be focused on the specific problems they want to prevent, claiming for specific prevention programs instead of non specific ones.